The Impact Of Leadership, Punishment, And Non-Physical Work Environment On Work Discipline And Employee Performance - Wiji Utami; Chaerul Saleh; Satrio Dwi Antoko (Jurnal Istiqro, 2018)
This research seeks to analyze the impact of leadership, punishment, and non-physical work environment on work discipline and employee performance in PT. Mitra Maju Mapan Jember. This research could be classified as explanatory research. Using cencus sampling method, the sample of this research was all the employee of PT. Mitra Maju Mapan totaling 87 respondens. The data was analyzed using path analysis. The result showed that leadership, punishment, and non-physical work environment have direct significant effect on work discipline, work discipline have direct significant effect on the employee performance, and leadership, punishment, non-physical work environment have indirect and significant effect on employee performance. This research contributes to knowledge regarding how to improve the work discipline among employee and further increase their performance. As a final point, it will be useful for further studies to compare the results of this study in different company to analyze the similarities and dissimilarities.